Art of Architecture in the Fatimiyyah Dynasty (697 -1171 AD) - Fatimatuz Zahro'; Afiful Aziz; Fatimatil Imroatil Karimah; Zulfi Mubarok; Syuhadak Syuhadak (UIN Sumatera Utara Medan, 2023)
The Fatimiyyah Dynasty was a vast and advanced country in several fields, especially in the field of architectural art. Founded by the Ismaili Shia sect. The writings of the research are first, wanting to understand concrete forms in the field of architectural art during the Fatimiyyah dynasty. second. want to understand the internal and external factors in the field of architectural arts during the Fatimiyyah dynasty. third, they want to understand the implementation of architectural art during the Fatimiyyah dynasty. The research methodology includes library research from primary data and secondary data relevant to the topics discussed. The results of this study are: first, concrete manifestations of the history of the Islamic civilization of the Fatimiyyah dynasty, namely the buildings of mosques, hotels, luxurious palaces, and forms of ornament and decoration. second, internal factors such as Islamic values contained in art, architectural art is knowledge from the Qur'an, and art cannot be separated from the local culture. External factors, namely the art of architecture, are influenced by the economy, international trade, and advances in science and technology. Third, this architectural art implies that the buildings at the Great Mahdiya Mosque, Al Azhar Mosque, Qarafa Mosque, Al-Hakim Mosque, and Other Cairo Mosques, Cairo Fort, Bab Al Futuh, Bab Al Nasr, and Bab Zuweil then form buildings like many passageways, a central courtyard surrounded by arcades, curly arches, portals, domes, ornate façades and architectural features of East and West.